Marketing Refurbished Products with Carbon-Emission-Constraint Policy and Consumer Behavior: Offline vs. Online Channels - Nughthoh Arfawi Kurdhi; Yahya Putra Pradana; Yogi Pasca Pratama; Vika Yugi Kurniawan ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2024)
Refurbished products, which are repaired or restored to a like-new condition, offer a more sustainable alternative to new products by extending their lifecycle. However, the marketing of refurbished products faces several chal-lenges, including consumer perception, trust, and the impact of carbonemission-constraint policies. This study aims to address these challenges and provide recommendations for effective marketing strategies. We explore the marketing of refurbished products within the context of carbon-emission-constraint policies, specifically comparing offline and online channels. We present two channel models, with the first model, referred to as Model O, fo-cusing on marketing refurbished products through the manufacturer’s own e-commerce channel. The second model, known as Model T, explores the al-ternative approach of outsourcing the marketing activity to a third-party en-tity. Carbon-emissionconstraint policies impose restrictions on businesses’ carbon footprint, affecting their marketing strategies. Businesses must navi-gate these policies while effectively promoting refurbished products to envi-ronmentally conscious consumers. By addressing the challenges faced in marketing refurbished products with carbon-emission-constraint policies, consumer behavior, and comparing offline and online channels, this thesis aims to provide valuable insights for businesses and policymakers to effec-tively promote sustainable consumption and contribute to a more environ-mentally conscious industry.